Surface roughness of different types of resin composites after artificial aging procedures: an in vitro study - Zeynep Biçer; Batu Can Yaman; Özge Çeliksöz; Hatice Tepe (BMC, 2024)
Abstract Background The temperature changes, chemical agents, and brushing activity that resin composite restorations are exposed to in the oral environment can cause changes in surface roughness. In this study, the aim was to investigate in vitro the clinical one-year surface roughness changes of different types of composites (flowable or conventional) from the same companies by subjecting them to immersion in solutions, brushing, and thermal cycling procedures to simulate intraoral conditions. Methods Four different resin composite brands were included in the study using both their conventional (Charisma Smart, 3M Filtek Ultimate Universal, Omnichroma, Beautifil II) and flowable resin composites (Charisma Flow, 3M Filtek Ultimate Flowable, Omnichroma Flow, Beautifil Flow Plus F00), giving 4 groups with 2 types of resin composite in each. 40 samples were prepared for each group/resin type, for a total of 320 samples. After initial surface roughness measurements by a mechanical profilometer, the samples were divided into 4 subgroups (n = 10) and immersed in solutions (distilled water, tea, coffee, or wine) for 12 days. The samples were then subjected to 10,000 cycles of brushing simulation and 10,000 cycles of thermal aging. Surface roughness measurements were repeated after the procedures. For statistical analysis, the 3-way analysis of variance and the Tukey test were used (p < 0.05). Results It was concluded that composite groups and types had an effect on surface roughness at time t0 (p < 0.001). At time t1, the highest surface roughness value was obtained in the Beautifil-conventional interaction. When the surface roughness values between time t0 and t1 were compared, an increase was observed in the Beautifil II and Beautifil Flow Plus F00, while a decrease was observed in the other composite groups. Conclusion Composite groups, types, and solutions had an effect on the surface roughness of resin composites. After aging procedures, it was concluded that the Beautifil group could not maintain the surface structure as it exceeded the threshold value of 0.2 μm for bacterial adhesion.